Gut metagenome‐derived signature predicts hepatic decompensation and mortality in NAFLD‐related cirrhosis. Issue 10 (26th September 2022) - Sharpton, Suzanne R.; Oh, Tae Gyu; Madamba, Egbert; Wang, Chenjingyi; Yu, Ruth T.; Atkins, Annette R.; Huan, Tao; Downes, Michael; Evans, Ronald M.; Loomba, Rohit
Summary: Background: There are limited data on the diagnostic accuracy of gut microbial signatures for predicting hepatic decompensation in patients with cirrhosis. Aims: To determine whether a stool metagenome‐derived signature accurately detects hepatic decompensation and mortality risk in cirrhosis secondary to non‐alcoholic fatty liver disease (NAFLD) Methods: Shotgun metagenomic sequencing was performed on faecal samples collected at study entry from a prospective cohort of adults with NAFLD‐related cirrhosis. A Random Forest machine learning algorithm was utilised to identify a metagenomic signature of decompensated cirrhosis (defined by ascites, hepatic encephalopathy or variceal haemorrhage) and subsequently validated in an external cohort. A Cox proportional hazards regression model was used to examine predictors of all‐cause mortality. Results: In all, 25 adults with NAFLD‐related cirrhosis (training cohort) were included. Among the 16 participants with decompensated cirrhosis, 33% had ascites, 56% had hepatic encephalopathy and 22% had experienced a variceal haemorrhage (not mutually exclusive). We identified a stool metagenomic signature comprising 13 discriminatory species that reliably distinguished decompensated NAFLD‐related cirrhosis (diagnostic accuracy, 0.97, 95% confidence interval [CI] 0.96–0.99). Diagnostic accuracy of the 13‐species signature remained high after adjustment for lactulose (area under the curve [AUC] 0.99) and rifaximin use (AUC 0.93). The discriminative ability of 13‐species metagenomic signature was robust in an independent test cohort (AUC 0.95, 95% CI 0.81–1.00). The 13‐species metagenomic signature (hazard ratio [HR] 1.54, 95% CI 1.10–2.15, p  = 0.01) was a stronger predictor of mortality than the Model for End‐Stage Liver Disease score (HR 1.25, 95% CI 1.03–1.53, p  = 0.03). Conclusions: This study provides evidence for a gut metagenome‐derived signature with high diagnostic accuracy for hepatic decompensation that predicts risk of mortality in NAFLD‐related cirrhosis. Abstract : Gut microbial signature in NAFLD‐related cirrhosis.